Peran Modal Sosial Dewan Adat Dayak(DAD) Kabupaten, dalam Melestarikan Kearifan Lokal di Kabupaten Lamandau, Provinsi Kalimantan Tengah - Djumaty, Brian L (Penerbit STKIP PGRI Bangkalan, 2019)
Today's development is so rapid that it is marked by changes in mindset, lifestyle etc., so that the scales cause negative impacts on the local wisdom of the people in Lamandau District, Central Kalimantan Province which results in an impact on endangered local wisdom. Departing from this problem, the aim of this study was to find out and analyze the role of social capital (bonding, bridging, networking) of the District Dayak Customary Council in preserving local wisdom in Lamandau District, Central Kalimantan Province. This research uses descriptive qualitative methodology. Using snowball sampling technique in determining informants. Based on the results of the study show that a). Bonding of social capital DAD Lamandau Regency lies in the homogeneous nature of its members. b). The position of Mr Marukan as Regional Head and Chair of DAD made the process of bridging (brigding) easier and could be well organized. c). DAD members who are also part of important stakeholders in Lamandau are important indicators that the community has as a form of the strength of DAD's social capital in building collaboration networks (linking social capital).